2022
DOI: 10.1002/ajh.26820
|View full text |Cite
|
Sign up to set email alerts
|

Moving toward more molecular classifications of myelodysplastic syndrome and acute myeloid leukemia

Abstract: The increase in our understanding of the genetic complexity of myelodysplastic syndromes (MDS) and acute myeloid leukemia (AML), as well at the rapid introduction of more targeted therapies for these diseases has made the diagnosis and classification of AML and MDS more challenging and nuanced. The third, fourth, and revised fourth edition World Health Organization (WHO) classifications, published by the International Agency on Cancer (IARC), have succeeded in incorporating new genetic criteria in the various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…One of the most important differences between the 2022 classifications is the introduction of AML- TP53 disease category in the ICC because of the negative prognostic role of biallelic TP53 mutations (or ≥10% variant allelic frequency) regardless of blast counts. 7 , 19 We found that ∼90% of AML with TP53 mutations were included in the AML-MR based on the WHO 2022 classification because of the coexistence of cytogenetic alterations, especially complex karyotype (81.8% of cases), and/or accompanying somatic MDS-related gene mutations ( supplemental Figure 3 ). 7 In this context, 9.4% of AML- TP53 , according to the ICC, would not emerge based on WHO 2022 rules.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…One of the most important differences between the 2022 classifications is the introduction of AML- TP53 disease category in the ICC because of the negative prognostic role of biallelic TP53 mutations (or ≥10% variant allelic frequency) regardless of blast counts. 7 , 19 We found that ∼90% of AML with TP53 mutations were included in the AML-MR based on the WHO 2022 classification because of the coexistence of cytogenetic alterations, especially complex karyotype (81.8% of cases), and/or accompanying somatic MDS-related gene mutations ( supplemental Figure 3 ). 7 In this context, 9.4% of AML- TP53 , according to the ICC, would not emerge based on WHO 2022 rules.…”
Section: Discussionmentioning
confidence: 93%
“…However, of 76 patients with RUNX1- mutated AML in our cohort, classified as having AML-MDSgene in the ICC, 77.6% were included in the WHO 2022 AML-MR category because of the presence of ≥1 additional MDS-related gene mutation. 19 Given the association of RUNX1 mutations with sAML and the evolution of bone marrow failure syndromes, examining for these mutations in the diagnostic process of AML may need to be reconsidered. 21 , 22 …”
Section: Discussionmentioning
confidence: 99%
“…By comparing the two works, we understand and appreciate the importance of molecular diagnostics and the scientific motivations assumed by the two groups in proposing their own rules and nomenclature. 20,21 This objective, however, is far from being achieved. Morphologists who operate in hematology laboratories were reassured by the agreement of both publications in much of the definition of myeloid and lymphoid subtypes.…”
Section: What Do We Continue To Do Today: In July 2022 the Proposed 5thmentioning
confidence: 99%
“…In both the new papers, the introduction declared that they aimed to propose a revision of the 2016 WHO classification based on scientific evidence. By comparing the two works, we understand and appreciate the importance of molecular diagnostics and the scientific motivations assumed by the two groups in proposing their own rules and nomenclature 20,21 . This objective, however, is far from being achieved.…”
mentioning
confidence: 99%